Foundation of Islamic Education Curriculum (Study of Q.S. Al-‘Alaq 1-5) Perspective of Transcendental Structuralism - Rahayu Subakat; Ahmad Yunus Mokoginta Harahap (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2022)
The researcher's academic anxiety sees the problem of lagging in Islamic education because the curriculum foundation is not strong. The existence of a long debate regarding the form of Islamic education curriculum demonstrates the confusion about the basic structure or foundation. Philosophically, Q.S. al-‘Alaq 1-5 contains the message of the basic values of Islamic education. The theoretical claim in this paper is Q.S. al-‘Alaq 1-5 which is elaborated on the theory of transcendental structuralism that produces the basic concepts of the Islamic education curriculum. Implicitly, this study can be used as a theoretical framework to analyze the problems of the Islamic education curriculum in general. This study aims to explain the relationship between Q.S. al-‘Alaq 1-5 with the foundation of the Islamic education curriculum. The results of this study indicate that based on Q.S. al-‘Alaq 1-5, the foundation of the Islamic education curriculum consists of epistemology as a way of thinking, world view as a view of world, and ideology as a value order oriented to the integration of spiritualawareness, rationality awareness, ethical awareness, technological awareness and awareness of social transformation. The novelty of this paper is found in the analysis of transcendental structuralism of the verses of the Qur'an which produces the theory of Islamic education. This research can be said as the theorizing of the Qur’an or the science of Islam.